High Diagnostic Accuracy of Visible 5‐ALA Fluorescence in Meningioma Surgery According to Histopathological Analysis of Tumor Bulk and Peritumoral Tissue. Issue 3 (1st July 2020) - Wadiura, Lisa I.; Millesi, Matthias; Makolli, Jessica; Wais, Jonathan; Kiesel, Barbara; Mischkulnig, Mario; Mercea, Petra A.; Roetzer, Thomas; Knosp, Engelbert; Rössler, Karl; Widhalm, Georg
Abstract : Background and Objectives: Complete neurosurgical resection of intracranial meningiomas is essential to avoid residual tumor tissue and thus minimize the risk of tumor recurrence. However, local recurrence of meningiomas is not uncommon mainly due to insufficient intraoperative detection of residual tumor tissue within the tumor bulk or peritumoral tissue such as bone and satellite lesions. Although 5‐aminolevulinic acid (5‐ALA) induced fluorescence was found to visualize the majority of meningiomas, no comprehensive histopathological assessment of fluorescing samples from the tumor bulk and peritumoral tissue is available. The aim of our study was thus to histopathologically analyze a large series of tissue samples derived from meningioma surgery to assess the positive predictive value (PPV) of visible 5‐ALA fluorescence. Study Design/Materials and Methods: In this study, we retrospectively investigated a series of tissue samples with visible 5‐ALA fluorescence collected during surgery of intracranial meningiomas from the tumor bulk and peritumoral tissue including the bone flap, dura/dural tail, arachnoidea, adjacent cortex, and satellite lesions. The tumor diagnosis was established according to the World Health Organization (WHO) criteria and all collected fluorescing samples were screened for presence of tumor tissue to calculate the PPV. Results: Altogether, 191 tissue samples with visible 5‐ALA fluorescence derived during surgery of 85 meningiomas (63 WHO grade I, 17 WHO grade II, and 5 WHO grade III) were included. In detail, 158 samples from the tumor bulk and 33 specimens from the peritumoral tissue were investigated. According to histopathological analysis, the PPV of 5‐ALA fluorescence was significantly higher in samples from the tumor bulk (100%) as compared with peritumoral tissue (73%; P < 0.001). With regard to peritumoral tissue, tumor tissue was present in most fluorescing samples from the satellite lesions (100%), the bone flap (92%), arachnoidea (83%), and dura/dural tail (75%). In contrast, tumor tissue was absent in the majority of samples from fluorescing cortex (six of seven samples; 86%). However, distinct reactive tissue alterations were found in all six tumor‐free fluorescing cortex samples and additional vascular proliferation in two cases. Conclusion: In this largest series to date, visible 5‐ALA fluorescence is characterized by a high PPV detecting tumor bulk and peritumoral tissue in intracranial meningiomas. Thus, 5‐ALA fluorescence supports the neurosurgeon in identifying residual tumor tissue at relevant surgical sites to optimize meningioma surgery and minimize the risk of local recurrence. © 2020 The Authors. Lasers in Surgery and Medicine published by Wiley Periodicals LLC